Ancient worlds in film and television : gender and politics - Renger, Almut-Barbara; Solomon, Jon (2012)
More than a century ago, filmmakers made their primary focus innovative and widely promulgated visions of antiquity, creating a profound effect on the critical, popular, and scholarly reception of antiquity. In this volume, scholars from a variety of countries and varying academic disciplines have addressed film’s way of using the field of Classical Reception to investigate, contemplate, and develop hypotheses about present-day culture, society, and politics, with a particular emphasis on gender and gender roles, their relationship to one another, and how filmic constructions of masculinity and femininity shape and are shaped by interacting economic, political, and ideological practices.